D4.2 Report of the 2nd summer school - Cerra, Daniele; Schreier, Gunter; Lysandrou, Vasiliki; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2017)
The specific deliverable summarizes the material related to the 2nd Summer School of the project entitled “Special issues of Optical Remote Sensing”. The deliverable contains actions completed prior the accomplishment of the Summer School, such as the agenda, while it also includes all the material delivered during the Summer School (e.g. presentations, supportive documents etc.), the list of participants and pictures from the event.
Keywords: Optical remote sensing; Summer school